CODE SWITCHING AND CODE MIXING IN BILINGUAL CLASSROOM INTERACTION - Andi Tenrisanna Syam (XXXXXXXX, 2023)
There are several international schools or even semi-international schools that utilize foreign language, especially the youth who has mastered their mother tongue sometimes (if not often) do code switch and/or code mix language to English alternately or in other words they change language occurring over sentences. The objective of this research was to find out code mixing and switching in terms of teacher talk and student talk used in the classroom interaction. The method of this research was qualitative quantitative and it applied discourse analysis approach. The subject of this research was the teacher and the students of Junior High School Number 12 Makassar. The researcher chose Biology teacher and took three classes. The instruments of the research were observation checklist, interview, recording, and questionnaire. The researcher found that the type token ratio in code mixing and code switching Indonesian/English in classroom interaction was varied. The average mean length of utterance of the teacher in code mixing and code switching Indonesian/English in the three classes were 11.77 in class VIIA, 11.23 in class VIIC, and 10.22 in class VIID. There were two types of questions the teacher asked in code mixing and code switching the words in the classroom namely convergent and divergent questions.  The teacher provided interactional feedback in code mixing and code switching to her students when addressing students in the classroom.Keywords: Code Mixing, Code Switching, Teacher Talk, Student Talk